2019
DOI: 10.3390/ijms20071585
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Transgene Suppression in Plants via External Application of Synthetic dsRNA

Abstract: Recent investigations show that exogenously applied small interfering RNAs (siRNA) and long double-stranded RNA (dsRNA) precursors can be taken up and translocated in plants to induce RNA interference (RNAi) in the plant or in its fungal pathogen. The question of whether genes in the plant genome can undergo suppression as a result of exogenous RNA application on plant surface is almost unexplored. This study analyzed whether it is possible to influence transcript levels of transgenes, as more prone sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 49 publications
0
71
1
Order By: Relevance
“…Suppression of root growth, seed germination, and failure of bolt or flower were detected along with silencing of the targeted genes (Li et al , ). Besides suppression of plant endogenous genes, a number of studies have demonstrated that direct application of dsRNAs can effectively silence transgenes such as GFP or YFP in plants (Dubrovina et al , ).…”
Section: Transportation Pathways Of Small Rnas In Plants and Fungimentioning
confidence: 99%
“…Suppression of root growth, seed germination, and failure of bolt or flower were detected along with silencing of the targeted genes (Li et al , ). Besides suppression of plant endogenous genes, a number of studies have demonstrated that direct application of dsRNAs can effectively silence transgenes such as GFP or YFP in plants (Dubrovina et al , ).…”
Section: Transportation Pathways Of Small Rnas In Plants and Fungimentioning
confidence: 99%
“…RNAi has been used to create a number of valuable traits in plants, and there is great potential for future applications to crop improvement (Frizzi and Huang 2010). Recently, plants have been shown to respond to RNA applied topically to leaf surfaces (Dalakouras et al 2016;Mitter et al 2017;Huang et al 2018;Niehl et al 2018;Sammons et al 2018;Dubrovina et al 2019), and this delivery route would expand the opportunities for using RNAi for agronomic benefit. In addition, topical delivery of sRNAs to plant cells provides a tool that can be used to investigate details of the RNAi mechanisms in plants.…”
Section: Introductionmentioning
confidence: 99%
“…dsRNAs targeted at virus replicase or coat protein genes was found to delay the development of disease, reduce infection symptoms and the number of infected plants, and decrease the virus titer [28,65]. In addition, it was confirmed that the protective effect induced by dsRNA or hpRNA lingers for at least 20-70 days after inoculation of the virus [72,98].…”
Section: Methods For Delivery Of Artificial Double-stranded Rnas In Pmentioning
confidence: 85%